Nepal-India Boundary Issue: River Kali as International Boundary - Manandhar, Mangal Siddhi; Koirala, Hriday Lal (Tribhuvan University Journal, 2011)
Not available. Key words: River; Nepal India Relations; International boundary Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 1-21 Uploaded date: 21 April, 2011